Inverse sine and cosine

  • Thread starter srini
  • Start date
  • #1
1
0
To show that
cos-1(-x)-cos-1(x)=2sin-1(x)

I tried
take x= sina
taking cos of the whole equation
cos(cos-1(-x))-cos(cos-1(x))=2cos(sin-1(x))
now we have to prove : -x-x=2cos(sin-1(x))
LHS: -2x=-2sina=2cos(a+pi/2)
RHS: 2cosa

Iam not sure how to proceed further..can anyone help me with this..
 
Last edited:

Answers and Replies

  • #2
marcusl
Science Advisor
Gold Member
2,762
412
To show that
cos-1(-x)-cos-1(x)=2sin-1(x)

I tried
take x= sina
taking cos of the whole equation
cos(cos-1(-x))-cos(cos-1(x))=2cos(sin-1(x))
This equation is incorrect. You need to expand cos(arcos(-x) - arcos(x)) properly,
You will then need to use relations like cos(arsin(y))=sqrt(1-y^2)
now we have to prove : -x-x=2cos(sin-1(x))
LHS: -2x=-2sina=2cos(a+pi/2)
RHS: 2cosa

Iam not sure how to proceed further..can anyone help me with this..
 
  • #3
Dick
Science Advisor
Homework Helper
26,260
619
You could also proceed more concretely. Get out (or make) a graph of cos^(-1) and sin^(-1) (let's call them acos and asin). If cos(theta)=x then cos(pi-theta)=(-x). So acos(-x)-acos(x)=pi-2*theta. Now if cos(theta)=x then sin(pi/2-theta)=x. So asin(x)=???.
 

Related Threads on Inverse sine and cosine

  • Last Post
Replies
1
Views
2K
  • Last Post
Replies
2
Views
2K
  • Last Post
Replies
1
Views
3K
  • Last Post
Replies
3
Views
6K
Replies
6
Views
2K
  • Last Post
Replies
14
Views
2K
  • Last Post
Replies
1
Views
11K
Replies
2
Views
2K
Replies
3
Views
2K
Replies
1
Views
682
Top